Prospects for digital economy in six countries in southeast Europe - Janevski, Zoran; Petkovski, Vladimir; Popovski, Vasil (Economic Development, Journal of the Institute of Economics – Skopje, 2017)
Progress made in storage, processing and transmission of digital data allowed merger of the departments of computerization, telecommunications and audio-video transmission, transforming into a significant sector of the digital economy. Advances in digital economy has realized a significant increase,1 implementing as an inevitable aspect in many parts of the society as retail, transportation, education, health, social interactions, banking and other elements. The growth of the digital economy is also driven, supported and facilitated throughout wide access to computers and the World Wide Web (Internet). In the world today, information and communication technologies are an integral part of the personal lives of people, businesses and governments, leading to convergence of ICT and the economy. Therefore, the aim of this paper is to consider the prospects of development of Digital economy in the six countries of Southeast Europe i.e. Republic of Macedonia, Slovenia, Serbia, Montenegro, Bosnia and Herzegovina and Croatia. According to this, a research has been conducted, in order to determine the prospects and possibilities for development of digital economy. The research was conducted using the comparison method, where the gathered NRI data (including four main categories and ten subcategories) for the six countries of the Southeast Europe where compared in order to determine the prospects for development of digital economy. The findings of this paper show us that the six European countries taken into consideration trail behind the in the majority of indicators. However, they each excel in different fields for development of the digital economy sector, and with mutual collaboration they could enhance and further increase the development of digital economy in their countries as well as the Southeast Europe region.
Keywords: digital economy, economic growth, innovation, technology, NRI index